Arthropod diversity in three different habitats around Sumbawa University Of Technology, Sumbawa, NTB - Fikri, Galih El; Arrufitasari, Putri Nur (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2024)
Arthropods have an important role in a habitat and food chain cycle. Identification of arthropod species abundance and diversity is done as a biological indicator of the environment. The aim of the research is determine the diversity and community structure of soil arthropods in various habitats and provide information on environmental quality caused by human activities around the campus of Sumbawa University of Technology. This research was conducted in three locations in the area around the Sumbawa University of Technology, Batu alang village, Moyo Hulu sub-district, Sumbawa district. The three locations include hillsides, campus areas and corn fields. Sampling of soil arthropods using the pitfall trap technique. Data on abundance, species richness, diversity, Calculation of the Index of Importance (INP) and diversity value (H') was analized by Excel. The results of Arthropod identification found a total of 2083 individuals consisting of 20 families and 8 Arthropod orders. The three sites showed that the abundance of arthropods in campus area was the highest at (212.75 ± 9.54) Arthropod species richness in corn field was the highest at 2.67 ± 0.4 Arthropod diversity (H’) in hilside was the highest at (3.23 ± 0.16). Campus area and corn field which have higher similarity.